(untitled) (American Journal of Islam and Society, 1989)
Introduction This work is concerned primarily with the activities of the Algerian ‘Ulama in the social and religious field. The most organized activities of Islamic reformism in Algeria started in 1931 with the establishment of the Association of the Algerian ‘Ulama. The ‘Ulama declared the ultimate goal of their Association to be only religious and cultural. The subsequent Islamic renaissance which they instituted in Algeria concentrated on the independence of the Muslim Creed, and social and cultural revivalism. The objective was to reform the practice of Islamic religion along the lines of the Islam of Suhjiyuh and not the Islam of Sufi sects. This was pursued by attacking the negative aspects of a1 vzwiiyuh (Sufi centers) and by encouraging the spread of al tu‘lim al hurr (the ‘Ulama type of education). The most significant role of al buthal dini (religious reformism) was that it ventured to prepare the Algerian masses for the violent conflict with France. Had it not been for this movement, the Algerian masses would have remained under the influence of the saints whose followers supported and consolidated the French colonial administration. In the following pages, the question will be posed as to how the liberation of Algeria was facilitated by the Algerian religious renaissance, which managed to liberate the consciousness of the masses. As a result, the Algerian masses were prepared morally and psychologically for political liberation from France. The Origins of Islamic Renaissance In Algeria The origins of the Islamic renaissance in Algeria were directly linked to the Suluflyuh movement, which flourished in ul Mushriq al Arubi during ...